The Development and Prospects of Socioscientific Issues Teaching in the Context of Immersive Media Technology - Kong, Zeming; Zhang, Shuya; Zhu, Fujin; Zhang, Junjun (Frontiers in Psychology, 2022)
Marshall McLuhan once proposed the concept of “global village,” believing that with the help of electronic media, Earth has become indistinguishable from a community, and there is only one Earth for human beings and one world for all countries. Today, with the continuous development of media technology, the concept of a human destiny community has also gained the general consensus of people around the world. The global value of the human destiny community encompasses the interdependent concept of international power, the concept of common interests, the concept of sustainable development, and the concept of global governance. In particular, the concepts of sustainable development and global governance have been advocated by the public, which in turn has led to extensive public discussions on Socioscientific Issues (SSI), in which the teaching of SSI is gradually considered by the international science education community as one of the important goals of science education. The current issues and challenges facing SSI teaching and how immersive media technologies can facilitate SSI teaching have become important issues of keen public interest.